Circulatory Arrest, Brain Arrest and Death Determination - Shemie, Sam David; Gardiner, Dale (Frontiers in Cardiovascular Medicine, 2018)
Remarkable technological advances, particularly in the capacity to support, replace or transplant failing organs, continue to challenge and refine our understanding of human death. Given the ability to reanimate organs after death, both inside and outside of the body, through reinstitution of oxygenated circulation, concepts related to death of organs (e.g. cardiac death) are no longer valid. This paper advances the rationale for a single conceptual determination of death related to permanent brain arrest, resulting from primary brain injury or secondary to circulatory arrest. In the setting of circulatory arrest, death occurs after the arrest of circulation to the brain rather than death of the heart. Correspondingly, any intervention that resumes oxygenated circulation to the brain after circulatory arrest would invalidate the determination of death.